Pengaruh Konsentrasi Perkursor terhadap Sifat Listrik dari Lapisan Tipis - Rindiani, Maiyola; Sanjaya, Hary; Budiman, Septian (Darul Yasin Al Sys, 2023)
A thin layer is a layer made from organic or non-organic materials which are semiconductors, conductors and insulators. This research aims to determine the effect of precursor concentration on the electrical properties of thin films. Variations in precursor concentration used were 0.025 M, 0.05 M, and 0.075 M. CuSnO3 thin films were characterized by UV-DRS, XRD, FPP, and SEM. The method used in this research is sol-gel. The sol-gel process is used because of its ability to control the surface properties of oxide composites. The results of the band-gap test the variation in precursor concentration obtained by the band-gap value becomes smaller with increasing concentration. The lowest band-gap value in variations in adding an MEA volume of 2 ml, the optimum band-gap value is 2.1706 eV. The results of the FPP test on a thin layer of CuSnO3 precursor concentration of 0.05 M with an optimum MEA of 2 ml obtained a resistivity value of 0.0005671 Ωm with a conductivity value of 173.5809 Ω^(-1) m^(-1).